Collisions and Competition of Legal Rules: General and Differences - Vladimir Valentinovich Kozhevnikov (Matondang Journal, 2024)
The problem of the relationship between the concepts of “conflict” and “competition” in law is considered. The purpose of the article is to substantiate the existing differences in legal conflicts and competition of legal norms. To achieve this goal, the following tasks have been set: 1) to reveal the etymology of the concepts “conflict” and “competition”; 2) analyze the views of legal scholars regarding the concept of conflict in law and its characteristics; 3) critically evaluate the positions of the authors who give examples of norms in which conflicts and competition in law are identified; 4) define the concept of competition in law, giving examples of criminal law norms; 5) objectively assess conflicts and competition in law from the point of view of legal regulation. The author of the study comes to the following conclusions: 1) legal conflicts and competition of legal norms are independent legal phenomena; they are united only by the fact that in both conflict and competition, the law enforcer must choose one of the norms to regulate the actual relationship; 3) legal conflicts and competition of legal norms differ: a) from the point of view of their assessment; b) from the point of view of their connection with the actual circumstances of the case: competition cannot exist in isolation from the actual circumstances of the case; conflicts of legal norms exist regardless of whether there are specific facts falling under these norms; 4) the problem of the relationship between legal conflicts and competition of legal norms has not only theoretical, but also practical significance.